Characterization and comparative analysis of volatile organic compounds in four aromatic wild strawberry species using HS-SPME-GC-MS - Linlin Xu; Wan Liu; Zhiliang Pan; Fuhua Pang; Yongqi Zhang; Jiahui Liang; Qinglian Wang; Jing Wang; Mizhen Zhao; Yushan Qiao; Huazhao Yuan (Food Chemistry: X)
Strawberries are valued for their aroma, which is mainly determined by volatile organic compounds (VOCs). Wild strawberries, with broader and more intense VOC profiles, are especially important in breeding programs. Using HS-SPME-GC–MS, 126 VOCs were identified in the ripe fruit of 22 cultivars from four wild strawberry species. Significant interspecies differences were found, with Fragaria mandshurica and F. nilgerrensis showing several times higher VOC levels than F. vesca and F. viridis, primarily due to high lactone content (up to 79.71 % of total VOCs). Phylogenetic analysis revealed conserved VOC profiles within species and genotype–aroma correlations. PCA and PLS-DA identified 60 biomarkers explaining 37.07 % of the variance, with 10 biomarkers validated for species identification, achieving 100 % accuracy. Key biomarkers for F. mandshurica included furaneol and perillyl acetate, while butanoic acid butyl ester was characteristic of F. vesca. This study emphasizes the role of VOCs as biomarkers for species differentiation and their potential in strawberry breeding.